CARCASS QUALITIES OF BROILER UNDER INTENSIVE AND BACKYARD SYSTEM OF MANAGEMENT IN MIZORAM - Fanai, r.; L, L. HMAR; Kalita, G.; Khate, K; Samanta, A.K (Indian Journal of Animal Production and Management, 2017)
Due to consumer appeal for higher fat deposit and preference of tougher meat andyellowish colour carcass by the Mizo people, broilers are reared up to 3- 4 months of age tillthey weigh around 4 - 5 kg. The study was conducted to compare the performance of broilerunder Intensive and Backyard System of management, for which 300 commercial broilerswere reared in three replicates (100 birds in one replicate) under Intensive System in theCollege farm and another 300 birds were reared at farmers level under Backyard System in10 replicates (30 birds / farmers). All the birds were reared up to 6th weeks of age and thirtybirds from each rearing system were randomly selected (10 birds per replicate fromIntensive System and 3 birds per replicate from Backyard System) and slaughtered to studysome important carcass characters. Remaining birds under both the rearing systems werereared up to 3 months of age and another similarly selected 60 birds (30 birds per rearinggroup) were utilized for carcass study. The live weights of broilers at 6th week and at 13thweek were significantly (P